Improving the Ability to Write Text Summaries of LHO Through the Problem-Based Learning Model - Monateni, Siane; Sapulette, Viona (Universitas Pattimura, 2025)
This study addresses the persistent problem of low summary writing abilities among secondary school students. The research aimed to improve the ability to write summaries of observation report texts (LHO) through implementing the Problem-Based Learning (PBL) model among Class VII-A students at SMP Kristen 1 Seram Barat. The study employed Classroom Action Research (CAR) methodology with data collection techniques including observation, interviews, questionnaires, and assignments. The research was conducted over two cycles, focusing on four key aspects: main ideas identification, text structure, diction, and Indonesian spelling (EYD). The study involved 32 Class VII-A students (16 male and 16 female students). Results demonstrated that the PBL model effectively improved students' summary writing abilities, with scores meeting the minimum competency standard of 72. Student performance showed significant improvement from Cycle I (average score of 60) to Cycle II (average score of 80), indicating good category achievement. The findings suggest that the problem-based learning model is particularly effective for teaching observation report text summarization skills in Indonesian secondary education contexts.